Effects of Apnea-Induced Hypoxia on Hypoalgesia in Healthy Subjects - Cristian Mendoza-Arranz; Omar López-Rebenaque; Carlos Donato Cabrera-López; Alejandro López-Mejías; José Fierro-Marrero; Francisco DeAsís-Fernández (Sports)
Introduction: Exercise-induced hypoalgesia is a phenomenon in which exercise bouts induce a reduction in pain sensitivity. Apnea training involves similar characteristics that could potentially induce hypoalgesia. Objectives: The objectives of this study are to explore the effect of apnea training on hypoalgesia; assess the correlation between conditioned pain modulation (CPM) response and apnea-induced hypoalgesia; and examine the association between hypoalgesia with hypoxemia, and heart rate (HR) during apnea. Methods: A randomized controlled trial was conducted comparing a walking protocol employing intermittent apnea compared with normal breathing in healthy volunteers. Hypoalgesia was tested with pressure pain thresholds (PPTs) and CPM. Oxygen saturation (SpO2) and HR were also tested. Results: Relevant but not significant changes were detected in the thumb (MD = 0.678 kg/cm2), and tibialis (MD = 0.718 kg/cm2) in favor of the apnea group. No significant differences were detected in CPM. The apnea group presented lower SpO2, but HR values similar to those of the control group during the intervention. Basal CPM and intrasession hypoxemia significantly correlated with the PPT response. However, HR did not correlate with the PPT response. Conclusions: The current results suggest a trend, though not statistically significant, toward an improvement in the PPT in favor of apnea training compared to normal breathing. Nevertheless, subjects who presented greater basal CPM and lower oxygen saturation during the session presented a greater PPT response, suggesting the possibility of mediators of response. Future investigations should clarify this phenomenon.